Keanekaragaman jenis dan karakteristik habitat nyamuk Anopheles spp. di Desa Datar Luas, Kabupaten Aceh Jaya, Provinsi Aceh - Riski Muhammad; Susi Soviana; Upik Kesumawati Hadi (Perhimpunan Entomologi Indonesia, 2015)
Malaria is a mosquitoe borne disease which still holds an impact position in public health sector in indonesia. The aims of this research are to study the diversity, density and behaviour of Anopheles, mapping its larvae habitat, and to measure the knowledge, attitudes and practices of the community in malaria endemic area at Datar Luas Village, Sub District Krueng Sabee, Aceh Jaya Regency. Mosquitoe trapping was done by landing collection inside and outside the house from 06:00 pm to 06:00 am WIB. In addition, larvae were collected and the coordinates of potential larva habitats were marked. There were eleven spesies of Anopheles, which were 45.9%, An. barbirostris and An. minimus 8.1%, An. maculatus, An. letifer, An. teselatus, An. sinensis, An. vagus, An. separatus 5.4%, An. sundaicus and An. subpictus 2.7%. The highest blood feed activity of An. kochi happened on 00:00–01:00 am WIB, An. minimus and An. barbiostris on 01:00–02:00 a.m WIB. There were four types of larvae i.e. pond, rain pudlles, marshes, and old well. An. letifer was found in pond, An. barumbrosus and An. kochi were in rain puddles, An. kochi, An. aconitus, An. vaguswere in them arshes, and An. separatuswas in old well.